2007
DOI: 10.1021/om701002k
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Synthetic Applications of 2,5-Bis(alkynylsilyl) Zirconacyclopentadienes

Abstract: 2,5-Bis(alkynylsilyl)-1-zirconacyclopentadienes 3 were formed highly regio- and chemoselectively in excellent yield by the homocoupling reaction of 2 equiv of bis(alkynyl)silanes 1 mediated by a low-valent zirconocene species (Negishi reagent) generated in situ from Cp2ZrBu2. Single-crystal X-ray structural analysis of 2,5-bis(phenylalkynyldimethylsilyl)-1-zirconacyclopentadiene (3a) revealed a sandwich-type conformation. Hydrolysis or halogenation of these zirconacyclopentadienes 3 afforded multisubstituted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 114 publications
1
5
0
Order By: Relevance
“…The rearrangement products derived from 1,1-bis(phenylethynyl)silanes give a distinct pattern for the former alkynyl carbons of resonances around 265, 210, 155, and 80 ppm for the Cp 2 Ti fragment and 255, 210, 160, and 100 ppm for Cp 2 Zr . Compounds 22 (Ti) and 24 (Zr) of this study also fall into these ranges.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…The rearrangement products derived from 1,1-bis(phenylethynyl)silanes give a distinct pattern for the former alkynyl carbons of resonances around 265, 210, 155, and 80 ppm for the Cp 2 Ti fragment and 255, 210, 160, and 100 ppm for Cp 2 Zr . Compounds 22 (Ti) and 24 (Zr) of this study also fall into these ranges.…”
Section: Resultssupporting
confidence: 50%
“…The reactions of 1,1-bis(alkynyl)silanes with titanocene and zirconocene , fragments have been studied for several cases. The outcome of the reaction of 21 with titanocene is characterized by the formation of the silacyclobutene-annelated titanacyclobutene complex 22 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…A novel twist on the reaction occurred when 0.5 equiv. of 'Cp 2 Zr' was reacted with R 2 Si(C À À À À À À CR 0 ) 2 (R¼ Ph, Me; R 0 ¼ Ph or alkyl; the same type of precursor used in both the Tamao and Wrackmeyer procedures) provided, after iodination, 1,4-diiodo-1,4-bis{(RC À À À À À À C) Me 2 Si} 2 -3,4-R 0 2 -butadiene [56]. Two reviews described butadiene building blocks and the synthetic applications of 1,4-dilithio-1,3-dienes [57a,b].…”
Section: Synthesis Of Siloles Using Transition Metal Reagentsmentioning
confidence: 99%
“…They also observed that the metal-to-diyne ratio played a key role in this zirconocene-mediated reaction of Si-tethered diynes. Upon increasing the ratio of Cp 2 ZrBu 2 : diyne from 2 : 1 to 1 : 1, reversible Si-C bond cleavage and formation was observed [54][55][56][57][58]. (10) According to their persistence, Xi and co-workers [59] developed the reaction of zirconacyclobutene-silacyclo butenes with nitriles into a versatile "tool-box" for preparation of various Si and N containing heterocycles.…”
Section: (3)mentioning
confidence: 99%